How γ-secretase hits a moving target - Sanders, Charles R (eLife, 2016)
An improved understanding of the ways that amyloid-beta peptides are formed could help efforts to find a treatment for Alzheimer’s disease.
Keywords: gamma-secretase; amyloid-beta peptides; intramembrane protease; Alzheimer's disease; presenilin; processive; C99